Differential inflammasome activation signatures following intracellular infection of human macrophages with Mycobacterium bovis BCG or Trypanosoma cruzi. (December 2016) - Huante, M.B.; Gupta, S.; Calderon, V.C.; Koo, S.J.; Sinha, M.; Luxon, B.A.; Garg, N.J.; Endsley, J.J.
Abstract: Pathogens frequently exploit or evade inflammasome activation in order to survive and proliferate. Alternatively, inadequate inflammasome activation by attenuated microorganisms or adjuvanted subunit vaccines may contribute to poor longevity of protection. To further understand these pathways, we determined the differential inflammasome transcriptome of human THP monocyte-derived macrophages in response to Mycobacterium bovis BCG, as compared to LPS or Trypanosoma cruzi . The results identify the highly specific innate recognition programs associated with inflammasome activation by human macrophages exposed to these microbial stimuli. BCG, T . cruzi, and LPS strongly induced expression of both unique and overlapping genes downstream of TLR signaling pathways including cytokines and chemokines that mediate inflammation and regulate cell death pathways. Compared to LPS, BCG failed to directly activate anti-apoptotic molecules and multiple NLR and inflammasome complex components including caspase-1, and actively repressed important signaling intermediates in AP-1 and NFκB transcription factor pathways. Both BCG and T . cruzi repressed expression of TXNIP, an anti-oxidant inhibitor that recruits caspase-1 to the NLRP3 inflammasome, while T . cruzi infection uniquely failed to activate TNF-α. These results identify unique pathogen specific strategies to activate inflammation and modulate cell death that may drive inflammatory outcomes and suggest avenues of investigation to optimize host immunity.